Globus Pallidus Internus Deep Brain Stimulation Using Frame-Based vs. Frameless Stereotaxy in Dystonia: A Single-Center Experience - Roberto Eleopra; Sara Rinaldo; Grazia Devigili; Massimo Mondani; Stanislao D'Auria; Nico Golfrè Andreasi; Miran Skrap; Christian Lettieri (Frontiers in Neurology, 2021)
Objective: Bilateral globus pallidus internus deep brain stimulation (GPi-DBS) is an established and effective therapy for primary refractory dystonia. However, the comparison of frameless vs. frame-based DBS surgery technique is still controversial. This retrospective study aims to compare the clinical outcome of two GPi-DBS surgical techniques for patients affected by primary generalized or multi-segmental dystonia.Methods: For lead's stereotaxic placement, 10 patients underwent frame-based surgery and the other 10 subjects DBS surgery with a frameless technique. Clinical features were evaluated at baseline and 6 and 12 months after surgery by means of the Burke–Fahn–Marsden Dystonia Rating Scale.Results: Frame-based GPi-DBS and frameless stereotaxic group revealed a comparable clinical outcome with no surgical complications.Conclusions: Frameless technique is safe and well-tolerated by patients and showed similar effectiveness of the frame-based stereotaxic surgery during GPi-DBS for primary dystonia. Notably, it could be a valid alternative solution because of the great advantage in improving the patient's discomfort during awake surgery.